Effect Of Organic Solvent On The Entrapment Of 25 Mole Percent Epoxidized Natural Rubber In Preformed Cyclomatrix Poly(1,3-Dioxybenzene) Cyclotriphosphazenes - Oh , Cheng Cheow (2009)

(untitled)
Blending of 25 mole percent epoxidized natural rubber (ENR-25) with preformed cyclomatrix poly(1,3-dioxybenzene)cyclotriphosphazene (P5) was carried out in toluene, methylene chloride, tetrahydrofuran, cyclohexane and 1,4-dioxane. Entrapment studies with the aid of Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) revealed that P5 can trap ENR-25 chains. The DSC and TGA data for [P5/ENR-25]b synthesized in all the studied solvents except toluene, revealed the presence of untrapped ENR-25. No untrapped ENR-25 is obtained in the DSC and TGA analysis results of the product synthesized in toluene, [P5/ENR-25]b-Toluene. As such, it can be concluded that synthesis in toluene lead to complete entrapment of ENR-25 in P5. The swelling of P5 in toluene facilitates the effective entrapment of ENR-25 chains into P5. The results of DSC analysis revealed the improvement in thermal properties of [P5/ENR-25]b-Toluene, with higher melting temperature (Tm) of 125 oC, as compared to that of the starting materials (with Tm of 117 oC for P5 and Tg of -44 oC for ENR-25). The results of FTIR analysis of the different products revealed no change in the functional groups of the ENR-25 entrapped in P5, as indicated by the insignificant shift of the absorption frequencies. Therefore it is likely that there is no chemical reaction involve in the entrapment of the ENR-25 chains in P5.